How to do this question. Please help me.
Attachments:
![](https://hi-static.z-dn.net/files/d4d/a33405ad04b18d0da44d493353b9984e.jpg)
Answers
Answered by
3
this is your answer....
Attachments:
![](https://hi-static.z-dn.net/files/d55/7aa52b65d084f58c801c046d3ef2196d.jpg)
Answered by
1
Factorize-
36 - (x²-8x+16)
= 6² - {(x)²-2×4×x+(4)²}
= 6² - (x-4)²
= (6+x-4) (6-x+4)
= (x+2) (10-x)
36 - (x²-8x+16)
= 6² - {(x)²-2×4×x+(4)²}
= 6² - (x-4)²
= (6+x-4) (6-x+4)
= (x+2) (10-x)
Lipimishra2:
Thank you for marking the best. :)
Similar questions